HBR guide to buying a small business - Ruback, Richard S. (Harvard Business Review Press, 2017)
Are you looking for an alternative to a career path at a big firm? Does founding your own start-up seem too risky? There is a radical third path open to you: You can buy a small business and run it as CEO. Purchasing a small company offers significant financial rewards―as well as personal and professional fulfillment. Leading a firm means you can be your own boss, put your executive skills to work, fashion a company environment that meets your own needs, and profit directly from your success